2018
DOI: 10.26540/ijgsr.v5.i1.2018.96
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Productivity of Wheat as Influenced by Tillage Methods, Mulch and Graded Nitrogen Levels in Chitwan, Nepal

Abstract: A field experiment was carried out to assess the growth and productivity of wheat as influenced by the tillage methods, mulch and graded nitrogen levels at the Agronomy Farm of Agriculture and Forestry University, Rampur during winter season of 2015/2016. The experiment was laid out in strip split plot design comprising tillage methods (zero tillage and conventional tillage) and mulch (mulch and no mulch) as horizontal and vertical factors, respectively and nitrogen levels as sub-sub plot factor (0, 50, 100 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Biomass yield was higher when the treatment had a combination of conventional tillage and residue retention, among others. Thapa et al [44] also found similar results where no-till plots had lower biomass yield compared to conventional till plots, however, a significantly higher biomass yield resulted in mulched plots in comparison to the nonmulched wheat.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Biomass yield was higher when the treatment had a combination of conventional tillage and residue retention, among others. Thapa et al [44] also found similar results where no-till plots had lower biomass yield compared to conventional till plots, however, a significantly higher biomass yield resulted in mulched plots in comparison to the nonmulched wheat.…”
Section: Discussionmentioning
confidence: 66%
“…Rieger et al [43] found that no-till system resulted in lower TKW compared to conventional tillage. Thapa et al [44] reported a significant difference in TKW with N management while no difference was observed among the tillage treatments Grain yield was found to be improved with CSAH and CSAM treatments. The increased yield in CSAH and CSAM treatments over farmers practice might be attributed to the inclusion of no-till and residue retention systems [45,46].…”
Section: Discussionmentioning
confidence: 96%